Multiprofessional hospital care in pediatrics in times of covid-19: scope review protocol (Research, Society and Development, 2022)
Multiprofessional assistance in the hospital environment brings together a range of actions depending on the area. In pediatrics, they provide care that also involves the companions. The pandemic brought countless restrictions that impacted hospitals in several areas. This review protocol aims to map and describe the scientific evidence on multidisciplinary care in pediatrics during the pandemic of covid-19. This is a protocol that will guide the scoping review that has as its research question “What is the scientific evidence about multiprofessional care in a pediatric hospital setting in times of a covid-19 pandemic?”. The protocol was designed based on the Joanna Briggs Institute (Peters et al., 2020) and systematized according to the recommendations of the Preferred Reporting Items for Systematic and Meta-Analyses – Extension for Scoping Reviews (PRISMA-ScR). Data will be collected in a form, organized by Rayyan and analyzed by IRaMuTeQ software. The selection of studies will occur in the national and international literature. The eligibility criteria will be: publications about multiprofessional hospital care in pediatrics during the covid-19 pandemic, from the beginning year, without limitation as to the languages. There will also be no limitation as to type, methodology or study design. Letters to the editor, abstracts in proceedings, incomplete articles, studies in project phase or without results will be excluded.